Gut Mucosal Microbiome Signatures of Colorectal Cancer Differ According to BMI Status - Shaw, Sophie; Berry, Susan; Thomson, John; Murray, Graeme I.; El-Omar, Emad; Hold, Georgina L. (Frontiers in Medicine, 2022)
Background Carrying excess body weight is a strong risk factor for colorectal cancer (CRC) development with 11% of CRC cases in Europe linked to being overweight. The mechanisms through which excess body weight influences CRC development are not well understood but studies suggest the involvement of the presence of chronic low-grade inflammation and changes in the gut microbiota are involved. Aim To compare the mucosal associated microbiota of patients with CRC to understand whether carrying excess body weight was associated with a unique CRC microbial signature. Methods Microbiota signatures from colonic mucosal biopsies of CRC lesions and adjacent normal mucosal samples from 20 patients with overt CRC were compared with 11 healthy controls to see if having a BMI of >25 kg/m2 influenced colonic microbial composition. Results Colonic mucosa samples from patients with CRC confirmed previously reported over-abundance of Fusobacteria associated with CRC but also an increase in Fusobacteria and Prevotella were associated with a BMI of >25 kg/m2. Correlation analysis of bacterial taxa indicated co-exclusive relationships were more common in CRC patients with a BMI >25 kg/m2 with an increase in transphylum relationships also seen in this patient group. Conclusions The findings suggest that gut microbiota composition in patients with CRC is influenced by BMI status. Further understanding/defining these differences will provide valuable information in terms of developing novel pre-onset screening and providing post-manifestation therapeutic intervention.